[PP.11.21] PREVALENCE OF RESISTANT AND REFRACTORY HYPERTENSION IN FRENCH PRIMARY CARE OFFICES. RESULTS FROM THE PASSAGE REGISTRY. (September 2017) - Mourad, J.J.; Le Jeune, S.; Pointeau, O.; Lopez-Sublet, M.
Abstract : Objective: Since 2000, very few registries evaluated the rate of BP controlled patients in general practice in France. The PASSAGE registry, conducted in 2014, demonstrated that 51.5% of treated patients were at goal. The aim of this additional analysis was to provide a more phenotype of this population, taking into account the BP level and the number of medications, according to a recently published classification (Dudenbostel T. Hypertension. 2016;67:1085). Design and method: A representative sample of 1000 French practitioners was requested to include the first consecutive 20 hypertensive patients. Controlled hypertension was defined as SBP <140 mm Hg and DBP <90 mm Hg in patients <80 yo and SBP<150 mmHg in patients >80 yo. The recruitment period held from november 2013 to february 2014. Patients were classified in 5 categories according to their BP level and antihypertensive treatment. Figure. No caption available. Results: 23406 patients (mean age 66 ± 12 y; 50.7% of males) were included. 14.2% were >80yo. 47% had treated dylipidemia and 11.6% were active smokers. Monotherapy, dual therapy were used in 48.7% and 31.8% respectively, whereas 3 treatments and more were prescribed in 16.4% of patients. Mean BP was 140 ± 16 / 80 ± 10 mmHg. According to the classification, 51.5% of patients had controlled hypertension, 1.9% had controlled controlled hypertension, 40.2% had uncontrolled hypertension, 6.3% had resistant hypertension, and 0.1% had refractory hypertension. Conclusions: This new classification makes it even better to clarify the status of blood pressure control at a population level. These findings underscore the overall therapeutic burden of hypertensive patients, who are generally under-treated, as evidenced by high rates of monotherapy, uncontrolled hypertension and low rates of resistant and refractory hypertension.